El efecto de extractos vegetales en el control del falso nematodo del nódulo de la raíz (Nacobbus spp.), en condiciones de laboratorio. - Pachacama Calero, Tania Elizabeth (2022)
The incidence of nematodes in crops is considered an important pest worldwide, since economic losses in agricultural production are close to 11%, productivity and profitability are minimized where the nematode is present. It is considered that under greenhouse conditions (Nacobbus spp) cause losses of 60 to 70% with only an average population, which is why it is considered a latent problem in agriculture. The research was carried out in the Microbiology laboratory of the Technical University of Cotopaxi, with the objective of evaluating the effect of plant extracts with concentrations of 25% and 10% in the control of the false root-knot nematode (Nacobbus spp. ) under laboratory conditions, including a control, where there were seven treatments arranged in a completely randomized design with three replications, in each treatment there were 25 individuals of the species under study, nematode extractions were performed from the affected roots and finally plant extracts were prepared from the flowers of (Nicotiana glauca), (Brugmansia arborea) and (Brugmansia sanguinea). Mortality data was collected every 8 hours after applying the treatments, where the dead individuals were counted up to 32 hours after applying the plant extracts. The results obtained determined that the plant extracts control Nacobbus spp, with an average of 23.5 individuals killed by (Nicotiana glauca), followed by 17.67 individuals killed by (Brugmansia arborea) and finally (Brugmansia sanguinea) with 13 individuals killed. The best concentration for the application of the extracts was at 25% with an average of 22.67 dead individuals and at 10% with an average of 13.44 dead individuals. For the interaction between plant extracts and concentrations, Nicotiana glauca at 25% concentration obtained the best average of 24.67 dead individuals 32 hours after the application of the plant extract.